PERBEDAAN PENGGUNAAN MODEL PEMBELAJARAN TALKING STICK DAN METODE CERAMAH TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM (PAI) SISWA DI SD IT TAHFIDZ AL FATIH PEKANBARU - Mawar Fita Sari; Risnawati; Miftahir Rizqa (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to determine the differences between the Talking Stick learning model and the lecture method on the learning outcomes of Islamic Religious Education (PAI) students at SD IT Tahfidz Al Fatih Pekanbaru. This research method is quantitative with a quasi-experimental nonequivalent control group design. The population of this study was all class II students and the sample was class II C, 19 students as the control group and class II D, 21 students as the experimental group. Data collection techniques use tests and observations. Data analysis techniques use descriptive analysis and t test. The results of this research are that the average posttest result for the experimental group is 86.14, which is higher than the control group, 73.75. The results of the t test with SPSS Statistics 21 obtained a t count of 2,718. The t table with df=18 at the 5% significance level is 0.14. This shows that the calculated t is greater than the t table, so Ha is accepted and H0 is rejected. The results of the t test obtained a significant count of 0.14, this value is smaller than 0.05 so that Ha is accepted and H0 is rejected. Based on these results, it can be concluded that there is a difference between the Talking Stick learning model and the lecture method on the learning outcomes of Islamic Religious Education (PAI) for class II students at SD IT Tahfidz Al Fatih Pekanbaru.